The Role of Digital Communication in Overcoming Polarization After the 2024 Presidential and Vice Presidential Debate - Suci Rahayu Maulidyah; Dhiny Nedyasari; Nanda Alif Andryanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The second Vice Presidential Candidate Debate in the 2024 General Election has the potential to cause polarization due to plural citizens/differences in society. Digital Communication, which has an educational function, is projected to be a mediator so that polarization can be minimized as much as possible. This research is a qualitative research with a descriptive approach regarding the role of digital communications in overcoming polarization following the debate for vice presidential candidates in the 2024 general election. The data that researchers use here is secondary data that researchers obtained from credible websites, books, scientific articles, and various other sources. which is commonly used in every other scientific research. The data in this research was analyzed using the stages of data collection, data selection, data reduction, and drawing conclusions. The result in this research show 1. Digital Communication can have a negative impact, namely causing polarization due to a society that is plural/full of differences if used in incorrect ways, provoking social rifts and conflicts, insulting each other, and so on. 2. Digital Communication can have a positive impact in order to minimize polarization in three ways, namely being used to create positive, non-provocative content, focusing on vision and mission, and debating substantive matters.